2021
DOI: 10.3390/ijerph18126404
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Effects of Unneeded Consumption Behaviour on Consumers during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has become an important global contagion that requires workers to implement necessary behaviours to cope. Based on the conservation of resources theory, the present studies explore the effects of unneeded consumption behaviour on consumers’ recovery level and work engagement and the moderated mediating process of such relationships. Using a purchasing experiment, study 1 examined the positive effect of unneeded consumption behaviour on recovery among 100 MBA students. Using the experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Other theories found in our other research are not many, only one publication such as the Conservation of Resources Theory conducted by (54)which examines the positive effects of unnecessary consumption behavior on consumers. during the Covid 19 pandemic.…”
Section: Classification Based On Theoretical Frameworkmentioning
confidence: 95%
“…Other theories found in our other research are not many, only one publication such as the Conservation of Resources Theory conducted by (54)which examines the positive effects of unnecessary consumption behavior on consumers. during the Covid 19 pandemic.…”
Section: Classification Based On Theoretical Frameworkmentioning
confidence: 95%
“…This anxiety of people decreased supply, increased prices, and created challenges for retailers and local governments (Gupta et al, 2021). The study by He et al (2021) added that the coronavirus outbreak may also lead to global shortages, making it difficult for retailers to shift inventory to support regional demands.…”
Section: Stockpiling Behaviormentioning
confidence: 99%
“…Customers who engaged in this type of buying behavior not only met their basic needs but also experienced the psychological reward of satisfying their impulses. Moreover, consumers prioritized psychological needs such as emotional value or optimistic feelings in the short term rather than rationalizing their purchasing decisions, such as determining if their behavior involves overconsumption (He et al, 2021).…”
Section: Consumer Cognition and Consumer Satisfactionmentioning
confidence: 99%
“…The "learning organizations" (cluster 24) can quickly adapt to the changes in the environment. Hence, it is another innovative practice facilitating work engagement as research found that learning organization drives engagement during the COVID-19 pandemic [98]. Besides, "concern for people who have high recovery capacities" (cluster 25) is another practice that can be used in driving employee engagement [99].…”
Section: Directing Employeesmentioning
confidence: 99%